Analisis kelayakan usaha kerupuk ikan di Kelurahan Tahtul Yaman Kecamatan Pelayangan Kota Jambi - Khairunnisa, Adnin; Gosari, B.A.J.; Fakhriyyah, S.; Hasani, M.Chasyim; Alpiani (Universitas Halu Oleo, 2024)
This study aims to determine the income level, business feasibility, and production and price of fish crackers in Tahtul Yaman Village, Jambi City, Servantgan District. Data collection is carried out through observation and survey methods. Once the data is collected, it is tabulated and analyzed using the revenue formula, R/C Ratio, and Break Even Point. The results showed that the income received was Rp18.270.000 for a year, the R/C Ratio value was 1.98, the BEP value of production was 132 kg, and the BEP price value was Rp35.338,-.